The analysis of bloodstain patterns as a key piece of evidence in the reconstruction of a murder - Álvaro Vázquez, Joaquín (Logos Guardia Civil, Scientific Magazine of the University Center of the Guardia Civil, 2026)
Bloodstain Pattern Analysis (BPA) is a fundamental tool for reconstructing the dynamics of violent events at crime scenes. This study presents the analysis and interpretation of bloodstain patterns documented in a homicide case that occurred in Zafra (Badajoz, Spain) in 2024, within the framework of a technical crime scene investigation conducted under a unified analytical approach and manual trigonometric methodology.Based on the morphology, distribution, and correlation of bloodstains with medico-legal findings, the sequence of events most consistent with the physical evidence is reconstructed, identifying the initial scene, the victim's movements, and subsequent phases of the event. Evidence consistent with scene alteration, including selective cleaning and re-entry, is also examined.This case is of particular interest from an evidentiary perspective, as it developed in a context characterized by limited conclusiveness of other forensic evidence and competing hypotheses. In this scenario, BPA played a central role in the overall assessment of the evidence. The scientific reliability of the discipline, its application within the Spanish procedural framework, the implications of expert communication before lay juries, and the inherent limitations of the analysis are also discussed.
Keywords: bloodstain pattern analysis; BPA; forensic reconstruction; forensic evidence; lay jury